Fragmented QRS and blood pressure pattern in normotensive individuals with a history of preeclampsia - Göçer, Kemal; Aksu, Ekrem; Erkayıran, Ugurkan (Journal of Surgery and Medicine, 2021)
Background/Aim: Hypertension is well defined in preeclamptic individuals and those with a history of preeclampsia. However, the relationship between blood pressure pattern and fragmented QRS on electrocardiography (ECG) has not been elucidated in normotensive patients with a history of preeclampsia. This study aimed to investigate the frequency of non-dipper blood pressure (BP) patterns in normotensive individuals with a history of preeclampsia and to evaluate the relevance of this pattern to fragmented QRS (fQRS). Methods: Sixty-three normotensive (office BP measurement) patients with a history of preeclampsia were included in this study between August 2020 and January 2021. These individuals underwent 24-hour ambulatory BP monitoring. The patients were divided into two groups as dipper and non-dipper, according to their BP patterns. The two groups were compared in terms of echocardiographic parameters, laboratory values, and QRS fragmentation on ECG. Results: Left ventricular diastolic dysfunction (LVDD) diagnosed by echocardiography (P= 0.015) and fQRS on ECG (P=0.002) were significantly higher in the non-dipper group than in the dipper group. Tricuspid regurgitation velocity (P=0.004) and average E/e’ ratio (P<0.001) were higher in the non-dipper group. Mitral E/A ratio (P=0.437) and left atrial volume index (P=0.439) were similar between the two groups in echocardiography. The fQRS, LVDD, triglyceride, and low-density lipoprotein were subjected to multivariate logistic regression analysis, and fQRS was found to be an independent predictor of the non-dipper BP pattern in women with a history of preeclampsia (P=0.023, OR=4.951, 95% CI:1.245-19.688). Conclusion: The presence of an fQRS pattern on the ECG is associated with a non-dipper BP pattern in normotensive individuals with a history of preeclampsia.